Rada Państwa Republiki Kuby jako przykład naczelnego organu prezydialnego w państwie socjalistycznym - Bury, Paweł (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
This article presents issues related to the functioning of the Council of State in the political system of the Republic of Cuba. The Council of State is a very specific body – on the one hand, the Constitution places it in the role of a parliamentary body, on the other hand, it provides the Council with a number of independent competences, including those typical of the head of state. The unambiguous definition of the Council’s character is also hindered by the fact that its President, entitled the “Head of State and Government” by the Constitution, also possesses some of the rights that traditionally belong to the head of state. All these elements make the Council an institution that does not have a proper equivalent in other socialist countries.
Keywords: head of state; presidential body; Republic of Cuba; Council of State